2010
DOI: 10.1371/journal.pntd.0000757
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the Asian 1 Genotype of Dengue Virus Serotype 2 in Viet Nam: In Vivo Fitness Advantage and Lineage Replacement in South-East Asia

Abstract: A better description of the extent and structure of genetic diversity in dengue virus (DENV) in endemic settings is central to its eventual control. To this end we determined the complete coding region sequence of 187 DENV-2 genomes and 68 E genes from viruses sampled from Vietnamese patients between 1995 and 2009. Strikingly, an episode of genotype replacement was observed, with Asian 1 lineage viruses entirely displacing the previously dominant Asian/American lineage viruses. This genotype replacement event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
137
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 23 publications
16
137
0
Order By: Relevance
“…Our data are in agreement with recent reports that E1-226V mutant CHIKV strains grouped into the Central/East/South African genotype and DENV-2 strains grouped into the Cosmopolitan genotype were predominant epidemic strains circulating in Singapore in 2009 (7,19). As various genotypic strains may differ in epidemic potential and virulence, molecular epidemiological surveillance can provide valuable information in decision making regarding patient care, outbreak investigation, and control measures (2,4).…”
supporting
confidence: 91%
“…Our data are in agreement with recent reports that E1-226V mutant CHIKV strains grouped into the Central/East/South African genotype and DENV-2 strains grouped into the Cosmopolitan genotype were predominant epidemic strains circulating in Singapore in 2009 (7,19). As various genotypic strains may differ in epidemic potential and virulence, molecular epidemiological surveillance can provide valuable information in decision making regarding patient care, outbreak investigation, and control measures (2,4).…”
supporting
confidence: 91%
“…All these isolates were clustered under the Asian genotype 1. Similar findings observed in previous studies have shown that Asian genotype 1 was the predominant genotype in Vietnam in previous years (Vu et al, 2010). This proved that genotype distribution of DENV-2 remained stable in Vietnam for long time.…”
Section: Discussionsupporting
confidence: 91%
“…In Thailand, the Asian/American genotype of Thai DENV-2 viruses, most likely co-circulated with the Asian genotype 1 for at least a decade prior to 1991, but then were replaced by the Asian 1 lineage from 1992 to 2006 (Lambrechts et al, 2012;Wittke et al, 2002). The same circumstance also occurred in Cambodia as only Asian genotype 1 virus has circulated since 2005 (Vu et al, 2010). This finding showed that Highlands's strains had shared the same genotype of DENV-2 in Laos, Thailand and Cambodia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…GIII was previously dominant, but surveillance data from the last 20 years, in the form of nucleotide sequences from collected isolates, have revealed a gradual replacement of GIII by GI such that the latter is now dominant or cocirculating with GIII in many JEV regions of endemicity and epidemicity (16)(17)(18)(19). In general, lineage replacement is a cause for concern as it can impact disease control measures, resulting in the irruption of new outbreaks (20,21). Thus, understanding the reasons behind the current genotype replacement event can yield valuable insight into the future control and eradication of JE diseases.…”
mentioning
confidence: 99%